Cross-talk between inflammation, coagulation/fibrinolysis and vascular access in hemodialysis patients - Costa, Elísio (2010)
This work aimed to study the association between fibrinolytic/endothelial cell function and inflammatory markers in chronic kidney disease (CKD) patients undergoing hemodialysis (HD) and recombinant human erythropoietin (rhEPO) therapies, and its relationship with the type of vascular access (VA) used for the HD procedure. As fibrinolytic/endothelial cell function markers we evaluated plasminogen activator inhibitor type-1 (PAI-1), tissue plasminogen activator (tPA) and D-dimers, and as inflammatory markers; C-reactive protein (CRP), soluble interleukin (IL)-2 receptor (s-IL2R), IL-6 and serum albumin levels. The study was performed in 50 CKD patients undergoing regular HD, 11 with a central venous dialysis catheter (CVC) and 39 with an arteriovenous fistula (AVF), and in 25 healthy controls. Compared to controls, CKD patients presented with significantly higher levels of CRP, s-IL2R, IL-6 and D-dimers, and significantly lower levels of PAI-1. The tPA/PAI-1 ratio was significantly higher in CKD patients. We also found statistical significant correlations in CKD patients between D-dimers levels and inflammatory markers: CRP, albumin, s-IL2R and IL-6. When comparing the two groups of CKD patients, we found that those with a CVC presented statistically significant lower levels of hemoglobin concentration and albumin, and higher levels of CRP, IL-6, D-dimers and tPA. Our results showed an association between fibrinolytic/endothelial cell function and increased inflammatory markers in CKD patients. The increased levels of Ddimer, tPA and inflammatory markers in CKD patients using a CVC, led us to propose a relationship between the type of VA chosen for HD, and the risk of thrombogenesis.